KETAHANAN MASYARAKAT DALAM MENGHADAPI BENCANA BANJIR DI KECAMATAN MAROS BARU KABUPATEN MAROS - K, Risna; Djasman, Siti Nurkhatifa; Wardani, Anggi Anugrah; Sumayyah, Sumayyah; Padli, Feri (Universitas Negeri Makassar, 2023)
Community Resilience in Facing Flood Disasters in Maros Baru District Maros, Regency. This research aims to determine the factors that influence and the level of community resilience in facing flood disasters in Maros Baru District. The method used in this research is a survey with qualitative methods. Data collection techniques use observation, interviews and documentation. The data analysis technique uses interactive analysis. The research results based on the results of data analysis show (1) factors that influence community resilience in facing flood disasters in Maros Baru District, Maros Regency, namely the capacity of the community to reduce risk or damage through mitigation and adaptation, the capacity to maintain basic functions and structure in a disaster situation, capacity to recover after a disaster event. Of the three factors that influence community resilience in facing flood disasters in Maros Baru District, Maros Regency, the first indicator, namely the capacity of the community to reduce risk or damage through mitigation and adaptation, is the most influential among the other two factors. (2) the level of community resilience in facing flood disasters in Maros Baru District, Maros Regency, which includes capacity, threats and vulnerabilities. Among these three indicators, capacity is the thing that has the most influence on the level of community resilience in facing flood disasters in Maros Baru District, Maros Regency.